Repurposing daclatasvir for MASLD Therapy—A promising step forward with challenges ahead - Pirola, Carlos Jose (2025)
The article discusses the potential of repurposing daclatasvir, an FDA-approved anti-HCV drug, for treating metabolic dysfunction-associated steatotic liver disease (MASLD) and its advanced form, metabolic dysfunction-associated steatohepatitis (MASH). The study by Shu et al. identifies daclatasvir as a potent inhibitor of perilipin-2 (PLIN2), a protein central to lipid droplet stability and metabolic homeostasis. Daclatasvir enhances MARCH6-mediated ubiquitination of PLIN2, leading to its degradation, which reduces lipid accumulation, inflammation, and fibrosis—key features of MASLD and MASH. Preclinical models demonstrate its ability to improve lipid metabolism, reduce inflammation, and alleviate liver fibrosis. Despite promising findings, challenges remain. Clinical trials are needed to validate its efficacy and safety in humans, as animal models cannot fully replicate the multifactorial nature of MASLD. Long-term safety and potential off-target effects also require evaluation, especially since PLIN2 may protect against other liver conditions. The study highlights the need for broader screening of FDA-approved drugs and exploration of alternative pathways for PLIN2 regulation. While daclatasvir shows promise, further research is essential to address these gaps and advance its clinical application for MASLD therapy. The findings underscore the potential of drug repurposing as a cost-effective strategy for unmet medical needs.